Laryngeal electromyography: Contribution to vocal fold immobility diagnosis - Kimaid, P. A T; Crespo, A. N.; Quagliato, E. M A B; Wolf, A.; Viana, M. A.; Resende, Luiz Antonio de Lima [UNESP] (My University, 2004)
Laryngeal Electromyography (LEMG) is a diagnostic test commonly used in patients with vocal fold movement disorder The aim of this study is to describe LEMG in patients with vocalfold immobility. A total of 55 dysphonic patients with vocal fold immobility diagnosed by laryngeal endoscopy were grouped according to probable clinical cause: 1) unknown; 2) traumatic; or 3) tumoral compression. They were submitted to LEMG by percutaneous insertion of concentric needle electrode. LEMG was conclusive in all patients and showed a majority with peripheral nerve injury. LEMG diagnosed peripheral nerve damage in 25 group 1, 12 group 2, and 11 group 3 patients. LEMG was normal in 4 patients, suggesting cricoarytenoid joint fixation. Central nervous system disorders was suggested in 2 and myopathic pattern in 1. As the major cause of vocal fold immobility is peripheral nerve damage, LEMG is an important test to confirm diagnosis.
Keywords: Electromyography; Laryngeal; adult; aged; arthropathy; central nervous system disease; compression; controlled study; diagnostic test; dysphonia; electrode; electromyography; endoscopy; female; human; larynx disorder; larynx injury; larynx tumor; major clinical study; male; myopathy; needle; peripheral nerve injury; vocal cord; Adolescent; Adult; Aged; Endoscopy; Female; Humans; Laryngeal Nerves; Male; Middle Aged; Prognosis; Recurrent Laryngeal Nerve; Vocal Cord Paralysis